The Effect of Leverage and Capital Intensity on Tax Avoidance With Profitability as a Moderating Variable (Empirical Study on Property and Real Estate Sector Companies Listed on the Indonesia Stock Exchange in 2018-2022) - Fani Perdana Nurmadjid; Wiwik Utami (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This study aims to analyze the effect of leverage and capital intensity on tax avoidance with profitability as a moderating variable in property and real estate sector companies listed on the Indonesia Stock Exchange (IDX) for the 2018-2022 period. The population of this study includes all property and real estate sector companies listed on the Indonesia Stock Exchange (IDX) for the 2018-2022 period. Samples were taken using a purposive sampling method with certain criteria, during the study period. Based on the established criteria for the use of panel data, the number of data that can be processed is 100 data. The analysis method used is panel data regression with a fixed effect model approach processed using Eviews 12. The results of the study show that: (1) Leverage has a positive effect on Tax Avoidance; (2) Capital Intensity also has a positive effect on Tax Avoidance. (3) Profitability is a moderating variable (Pure Moderation) Where profitability is able to moderate the effect of Leverage on Tax Avoidance; (4) Profitability is a moderating variable (Pure Moderation) where profitability is able to moderate the influence of Capital Intensity on Tax Evasion.